Diaspora of Energy: A Case of Oil Production and Consumption - Khurshid, Muzammil; Azeem, Muhammad; Ahmad, Nisar; Rehman, Jamshaid Ur; Umar, Sajjad (International Journal of Energy Economics and Policy, 2024)
The study evaluates the nexus among oil prices, macro-economic indicators and stock returns of three Asian emerging oil-importing and three Asian emerging oil-exporting economies over a period from 2014 to 2019 on monthly observations. The study has made use of measure of association by applying VAR methodology. The results of the study indicate that oil prices movements have substantial impact on stock market trends whereas, the said impact varies depending upon the inherited macroeconomic condition of county. As regarding the oil-exporting countries the movement of oil prices is also equally important for the stock market behavior.